MRI assessment on the impact of a low FODMAP diet on the gastrointestinal tract - Krishnasamy, Shanthi (2019)
Introduction: Poorly absorbed fermentable carbohydrates (FODMAPs) escape digestion in the small bowel, and enter the colon to be fermented by gut bacteria thus increasing luminal volume. However, in susceptible individuals e.g. Irritable Bowel Syndrome (IBS) sufferers, this may result in gastrointestinal symptoms, due to the rapid emptying of the small bowel producing increased luminal water and distension in the colon from gas producing bacteria. Previous studies have demonstrated the effect of fermentation on FODMAPs by assessing microbial concentration and breath hydrogen. However, the physiological changes in the lumen, particularly in the colon, remain unclear.